2006
DOI: 10.1016/j.brainres.2006.05.104
|View full text |Cite
|
Sign up to set email alerts
|

Exact and approximate judgements of visual and auditory numerosity: An fMRI study

Abstract: Human adults can assess the number of objects in a set (numerosity) by approximate estimation or by exact counting. There is evidence suggesting that numerosity estimation depends on a dedicated mechanism that is a-modal and non-verbal. By contrast, counting requires the coordination between the pre-existing numerosity estimation abilities with language and one-to-one correspondence principles. In this paper we investigate with fMRI the neural correlates of numerosity estimation and counting in human adults, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
164
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 67 publications
18
164
1
2
Order By: Relevance
“…As in the case of perceptual comparisons, the pattern of difficulty for symbolic comparisons suggests that internal magnitudes are typically compressed such that subjective magnitude differences decrease as the absolute magnitudes of the objects being compared increase (Shepard, Kilpatric, & Cunningham, 1975). More recent work has provided strong evidence that humans and other primates are equipped with specialized neural circuitry for dealing with approximate magnitude on various dimensions (e.g., Cantlon, Brannon, Carter, & Pelphrey, 2006;Dehaene & Changeux, 1993;Piazza, Izard, Pinel, Bihan, & Dehaene, 2004;Piazza, Mechelli, Price, & Butterworth, 2006;Piazza, Pinel, Le Bihan, & Dehaene, 2007;.…”
Section: Alternative Models Of Symbolic Magnitude Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of perceptual comparisons, the pattern of difficulty for symbolic comparisons suggests that internal magnitudes are typically compressed such that subjective magnitude differences decrease as the absolute magnitudes of the objects being compared increase (Shepard, Kilpatric, & Cunningham, 1975). More recent work has provided strong evidence that humans and other primates are equipped with specialized neural circuitry for dealing with approximate magnitude on various dimensions (e.g., Cantlon, Brannon, Carter, & Pelphrey, 2006;Dehaene & Changeux, 1993;Piazza, Izard, Pinel, Bihan, & Dehaene, 2004;Piazza, Mechelli, Price, & Butterworth, 2006;Piazza, Pinel, Le Bihan, & Dehaene, 2007;.…”
Section: Alternative Models Of Symbolic Magnitude Comparisonsmentioning
confidence: 99%
“…More broadly, neural and other evidence indicates that primates have evolved a specialized system for processing approximate magnitude, in which the intraparietal sulcus plays a key role (e.g., Cantlon et al, 2006;Dehaene & Changeux, 1993;Piazza et al, 2004Piazza et al, , 2006Piazza et al, , 2007Pinel et al, 2004).…”
Section: The Power and Limits Of Magnitude Representationsmentioning
confidence: 99%
“…In contrast, prior neuroimaging work has suggested that brain regions that support language-especially regions on the lateral surface of the left frontal lobe-also support nonlinguistic functions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, the neuroimaging claims are based largely on observations of activation for a nonlanguage task in or near a general brain region previously implicated in language (e.g., Broca's area), without a direct demonstration of overlap of linguistic and nonlinguistic activations in the same subjects.…”
mentioning
confidence: 95%
“…Pasini and Tessari (2001) suggested left hemispherical specialisation for subitizing and right hemispherical specialisation for counting. A study by Piazza, Mechelli, Price, and Butterworth (2006) reported left hemispherical specialisation for approximate numerosity judgement in both vision and audition. If a similar or even a single mechanism underlies both visual and auditory numerosity judgement, it is likely that this mechanism also extends to the haptic modality.…”
Section: Introductionmentioning
confidence: 99%